The transition from iron starvation to iron sufficiency as an important step in the progression of infection. (1st December 2014) - Dauros-Singorenko, Priscila; Swift, Simon
Iron is an essential micronutrient for microbial life. At the start of an infection the host environment will normally restrict available iron, and innate immune responses will aim to further reduce iron, thus inhibiting growth of potential pathogens. Successful pathogens have developed a variety of mechanisms to acquire iron from the available in vivo sources, using remote and direct capture, to render their environment iron replete. Iron restriction, and the presence of host iron sources like haem, are important drivers of gene regulation controlling the expression of numerous virulence factors. As an infection progresses the changing iron environment will therefore influence pathogen gene expression and trigger new activities. Understanding how bacteria acquire iron, and how iron acquisition affects the bacteria, has identified vaccine and antibiotic drug targets and is now suggesting novel approaches to control and treat infection.